2016
DOI: 10.1186/s12903-016-0259-z
|View full text |Cite
|
Sign up to set email alerts
|

Immediate versus delayed loading of strategic mini dental implants for the stabilization of partial removable dental prostheses: a patient cluster randomized, parallel-group 3-year trial

Abstract: BackgroundAcceptable short-term survival rates (>90 %) of mini-implants (diameter < 3.0 mm) are only documented for mandibular overdentures. Sound data for mini-implants as strategic abutments for a better retention of partial removable dental prosthesis (PRDP) are not available.Methods/designThe purpose of this study is to test the hypothesis that immediately loaded mini-implants show more bone loss and less success than strategic mini-implants with delayed loading. In this four-center (one university hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
6
0
2
Order By: Relevance
“…Nevertheless, long-term survival rate studies for MDIs are still lacking. The high short-term survival rates of MDIs were only recorded for mandibular overdentures, whereas for maxillary overdentures retained by the MDIs, the short-term survival rates were significantly lower, ranging from 54 to 85% ( 27 , 28 ). In a study by Maryod et al, delayed loading of MDIs showed better MDI survival rate and less bone loss in comparison to immediate loading in the mandible ( 15 ).…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, long-term survival rate studies for MDIs are still lacking. The high short-term survival rates of MDIs were only recorded for mandibular overdentures, whereas for maxillary overdentures retained by the MDIs, the short-term survival rates were significantly lower, ranging from 54 to 85% ( 27 , 28 ). In a study by Maryod et al, delayed loading of MDIs showed better MDI survival rate and less bone loss in comparison to immediate loading in the mandible ( 15 ).…”
Section: Introductionmentioning
confidence: 94%
“…Despite the fact that all these improvements have contributed to the increase in the survival rate of dental implants, and therefore to make possible the application of surgical and prosthetic protocols that were previously considered high-risk, such as the immediate placement of implants in fresh post-extraction sockets 2 , 11 , 14 and the immediate functional loading, 15 , 16 unfortunately there is a percentage of implant failures which appear to be difficult to resolve. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a 3-year randomized clinical trial (RCT) was completed, comparing immediate with delayed loading of strategic MIs under existing RPDs with unfavorable tooth distribution [30]. The primary outcome was the radiological bone level change at MIs.…”
Section: Introductionmentioning
confidence: 99%